2022
DOI: 10.3389/fphys.2022.917203
|View full text |Cite
|
Sign up to set email alerts
|

The F1Fo-ATPase inhibitor protein IF1 in pathophysiology

Abstract: The endogenous inhibitor of ATP synthase is a protein of about 10 kDa, known as IF1 which binds to the catalytic domain of the enzyme during ATP hydrolysis. The main role of IF1 consists of limiting ATP dissipation under condition of severe oxygen deprivation or in the presence of dysfunctions of mitochondrial respiratory complexes, causing a collapse in mitochondrial membrane potential and therefore ATP hydrolysis. New roles of IF1 are emerging in the fields of cancer and neurodegeneration. Its high expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…IF1 is overexpressed in many human tumors [ 13 , 15 , 29 , 55 ] and different hypotheses on its pro-oncogenic role have been proposed [ 13 , 16 , 29 ], although its mechanism of action is still debated. MEFs overexpressing IF1, IF1 KD, and IF1 KO HeLa cells showed that colony formation in soft agar depends on IF1 expression level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IF1 is overexpressed in many human tumors [ 13 , 15 , 29 , 55 ] and different hypotheses on its pro-oncogenic role have been proposed [ 13 , 16 , 29 ], although its mechanism of action is still debated. MEFs overexpressing IF1, IF1 KD, and IF1 KO HeLa cells showed that colony formation in soft agar depends on IF1 expression level.…”
Section: Discussionmentioning
confidence: 99%
“…IF1 may also play a role in promoting cancer development and growth [13,14]. Its high expression level has been found in different human tumors [15], although the mechanism through which IF1 promotes cancer growth and progression remains debated [16]. Recent findings suggest that IF1 might bind to ATP synthase when the enzyme works physiologically [i.e., ATP synthesis [17][18][19][20]] and that its role in preventing ATP hydrolysis is observed only under anoxia/near-anoxia [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, ATP synthase activity has been associated with proliferation, invasive capacity, and apoptosis resistance in cancer cells [ 33 , 38 , 40 ]. Indeed, most cancer cells rely on aerobic glycolysis and many of them overexpress the ATPase inhibitor factor 1 (IF1), which affects cancer development through different effects such as cristae shaping or inhibition of ATP hydrolysis, among others [ 56 ]. In addition, several mt-ATP6 mutations have been detected in different human cancer cell lines and solid tumors [ 57 , 58 , 59 , 60 ], next to the 8414 position and affecting aH5 helix ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that several tumor types such as colon, lung, breast, and ovarian carcinomas upregulate the expression of ATPase inhibitory factor 1 (IF1) [ 38 ] which favors cell proliferation by blocking ATP hydrolysis and, consequently, preserving the amount of ATP [ 38 , 39 ]. More recently, different effects of IF1 on cancer development have been proposed [ 56 ]. In this sense, IF1 has been reported to have effects on metastasis promotion and cristae shaping [ 68 , 69 ], as well as on inhibition of ATP hydrolysis and escape from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The online resource inside this figure was quoted or modified from Servier Medical Art the rapid development and application of proteomic techniques, multiple omics have uncovered the distinctive mechanism inside complex III during cardiac aging. Likewise, the activity of ATP synthase [also known as complex V] is negatively correlated with aging, 217,218 resulting in a substantial decrement in the efficiency of OXPHOS. Moreover, complex V serves as a potential locus of the mitochondrial permeability transition pore (mPTP), 219 while defective complex V restrains the formation of mPTP and limits the coupling of OXPHOS to the ETC.…”
Section: Electron Transportmentioning
confidence: 99%